The fate of surplus embryos: Ethical and emotional impacts on assisted reproduction - Machado, Cynthia Silva [UNESP] (GN1 Sistemas e Publicacoes, 2020)
Objective: This paper looked into the findings of a survey on the ethical and emotional aspects encircling the fate of surplus embryos in Assisted Human Reproduction (AHR). Methods: Five staff members of a fertility clinic in the Brazilian State of São Paulo answered a semi-structured qualitative interview. Results: The answers alluded to the different mean-ings assigned to embryos by medical staff (genetic mate-rial) and couples undergoing fertility treatment (potential child). The meaning couples assigned to their embryos, along with inherent uncertainty and distress, affected the choice of what would be done to surplus embryos. Conclusion: Psychological support may be helpful to two key groups present in assisted human reproduction: clinic staff, for support in their interactions with couples; and couples in need of support and awareness on surplus embryo donation.
Keywords: Assisted human reproduction; Counseling; Embryo cryo-preservation; Embryo donation; Ethical and emotional as-pects